Molecular Characterization and Functional Analysis of Leucine Zipper Transcription Factor Like 1 in Zebrafish (Danio rerio) - Wei, Qun; Chen, Yongxia; Gu, Yi-Feng; Zhao, Wenhe (Frontiers in Physiology, 2019)
Leucine zipper transcription factor like 1 (LZTFL1) is a member of the Bardet–Biedl syndrome gene family. LZTFL1-null mice show the phenotype of obesity, retinal degeneration, and abnormal cilia development. Functionally, LZTFL1 serves as a tumor suppressor and a negative regulator in the hedgehog signaling pathways. The biological function of mammalian LZTFL1 is partially addressed, but data on other model organisms are limited. Zebrafish (Danio rerio) is widely considered as a powerful model to understand the functions of genes implicated in obesity, disease, and cancer. In this study, LZTFL1 homologs were identified in zebrafish (ZeLZTFL1). The full-length cDNA of ZeLZTFL1 contained 897 bps encoding 298 amino acids. ZeLZTFL1 displayed conserved domains of coil–coil and leucine zipper domain. PCR results showed that ZeLZTFL1 was widely distributed in various tissues. Western blot analysis further revealed that ZeLZTFL1 was detected to be ectopically expressed in HeLa cells with correct molecular weight. Fluorescence images showed as well that ZeLZTFL1 was localized in the cytoplasm. Furthermore, luciferase reporter assay indicated ZeLZTFL1 served as a negative regulator in the hedgehog signaling pathway. These data supported that zebrafish was a good model for understanding the biological roles of LZTFL1.